Perilaku Ramah Lingkungan yang Berkelanjutan di Kalangan Generasi Muda Konsumen - Amalia Sholikhah; Sri Vandayuli Riorini; Virginia Balqqis Zacqualine; Raihan Rizki Fajri (ManBiz: Journal of Management and Business, 2025)
This study aims to examine the influence of campus environment on the green behavior of young consumers. Using the framework of social cognitive theory (SCT) and value-belief-norm theory (VBN), this study explores the factors that mediate the relationship between campus advertising and pro-environmental intentions. Data were obtained from 120 respondents aged 18-23 years old and analyzed using structural equation modeling (SEM) method. The results show that campus advertising has a significant effect on pro-environmental behavior intention through responsibility attribution and personal norms.